2011
DOI: 10.1002/cncr.25834
|View full text |Cite
|
Sign up to set email alerts
|

Nodal yield and survival in oral squamous cancer

Abstract: BACKGROUND: Elective neck dissection (END) is commonly used as a staging and therapeutic procedure for oral squamous cell carcinoma (SCC) at high risk of nodal metastases. The authors aimed to determine whether the extent of lymphadenectomy, as defined by nodal yield, is a prognostic factor in this setting. METHODS: A retrospective database review identified 225 patients undergoing END with curative intent for oral SCC between 1987 and 2009. Nodal yield was studied as a categorical variable for association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
168
8
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(184 citation statements)
references
References 54 publications
4
168
8
4
Order By: Relevance
“…On the one hand, selective ND is feasible and safe, but on the other hand the number of excised nodes may impact on survival. Ebrahimi et al [55] reported that nodal yield is an independent prognostic factor in patients undergoing ND. In their retrospective analyses on 225 patients, nodal yield <18 was associated with a 5-year OS of 51% compared with 74% in those with nodal yield >18 (p = 0.009).…”
Section: Neck Dissectionmentioning
confidence: 99%
“…On the one hand, selective ND is feasible and safe, but on the other hand the number of excised nodes may impact on survival. Ebrahimi et al [55] reported that nodal yield is an independent prognostic factor in patients undergoing ND. In their retrospective analyses on 225 patients, nodal yield <18 was associated with a 5-year OS of 51% compared with 74% in those with nodal yield >18 (p = 0.009).…”
Section: Neck Dissectionmentioning
confidence: 99%
“…The debate on the usefulness of ND leads to a model to predict how many nodes are needed to prevent one fatal neck recurrence after CRT for HNC. As in the results of a study conducted by Javidnia et al [46], it was hypothesized that it is necessary to treat 7.5 patients to prevent one fatal neck recurrence after CRT for HNC with N2–3 disease. In the 2009 update of guidelines on behalf of the American Head and Neck Society, clinicians were encouraged to perform selective ND.…”
Section: The Timing Of Nd After Crtmentioning
confidence: 84%
“…On the one hand is the risk of neck recurrences or microscopic residual disease, on the other hand is the probability of an overtreatment with possible surgical complications (lymphedema, dysphagia, fistulae) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72]. Benefits may include local regional control and OS [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,…”
Section: Introduction: Pros and Consmentioning
confidence: 99%
“…There is a recent report that the number of lymph nodes found in the neck dissection is a prognostic factor of mouth cancer 2 . Patients with less than 18 lymph the nine cases of patients who developed isolated regional recurrences, all had 20 or more lymphnodes upon neck dissection.…”
Section: Discussionmentioning
confidence: 99%